2023
DOI: 10.1039/d2nr06372g
|View full text |Cite
|
Sign up to set email alerts
|

Valid design and evaluation of cathode and anode materials of aqueous zinc ion batteries with high-rate capability and cycle stability

Abstract: Although non-aqueous lithium-ion batteries have a high gravimetric density, recently aqueous zinc-ion batteries (ZIBs) have been in the spotlight as an alternative. Because ZIBs have characteristics such as high volumetric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Moreover, after the electrochemical process at high current densities, nearly 91.8% of the discharge capacity is recovered at 0.2 A g –1 for the NNVO, demonstrating good reversibility. Moreover, NNVO exhibits the competitive Zn 2+ storage performance to some reported materials, as compared in Figure f. Figure g shows the cycling performance at 5.0 A g –1 for NNVO. An impressive discharge capacity of 306.8 mAh g –1 in the initial cycle is delivered, and it reaches 325.5 mAh g –1 after the first 50 cycles with gradually improved material activation and electrolyte wetting.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, after the electrochemical process at high current densities, nearly 91.8% of the discharge capacity is recovered at 0.2 A g –1 for the NNVO, demonstrating good reversibility. Moreover, NNVO exhibits the competitive Zn 2+ storage performance to some reported materials, as compared in Figure f. Figure g shows the cycling performance at 5.0 A g –1 for NNVO. An impressive discharge capacity of 306.8 mAh g –1 in the initial cycle is delivered, and it reaches 325.5 mAh g –1 after the first 50 cycles with gradually improved material activation and electrolyte wetting.…”
Section: Resultsmentioning
confidence: 83%
“…[72] For example, an Al 2 O 3 -coated Zn anode was prepared by ALD. [73] In the synthesis process, Al(CH 3 ) 3 and H 2 O were alternately introduced into the reactor with Ar purging to form an Al 2 O 3 layer on the surface of the Zn anode (Al 2 O 3 @Zn) (Figure 8a). The thickness of the coating had a significant effect on the cycling stability, whose thickness was controlled by the number of ALD cycles.…”
Section: Atomic/molecule Layer Depositionmentioning
confidence: 99%
“…From the SEM images, it could be observed that the surface was covered by by-products on the bare Zn, while the surface of the ZrO 2 @Zn remained Reproduced from ref. [73] Copyright (2023), with permission from The Royal Society of Chemistry. c) Schematic illustration of the fabrication process of the inorganic ZrO 2 coating on Zn metal anodes by ALD.…”
Section: Atomic/molecule Layer Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Moreover, Zn metal, which is a type of multivalent ion battery anode material, has a high theoretical capacity (5855 mA h mL −1 and 820 mA h g −1 ) and a low redox potential (−0.76 V vs. the standard hydrogen electrode, SHE). 9–13 However, the Zn anode suffers from the least desirable side reactions, such as corrosion, dendrite growth, and hydrogen evolution reaction. 14–16 These problems result in poor reversibility, poor coulombic efficiency (CE), and limited cycle life of AZIB.…”
Section: Introductionmentioning
confidence: 99%